“Just Throw It Behind You and Just Keep Going”: Emotional Labor when Ethnic Minority Healthcare Staff Encounter Racism in Healthcare - Ahlberg, Beth Maina; Hamed, Sarah; Bradby, Hannah; Moberg, Cecilia; Thapar-Björkert, Suruchi (Frontiers in Sociology, 2022)
Encountering racism is onerous and meeting it in a health care setting is no exception. Ethnic minority health care staff who encounter racism during their work described the significant emotional labor involved in dealing with racism. This emotional labor arises for two distinct reasons. The first is the concern and fear of consequences for their employment should they be seen to discuss racism. The second concerns the ethical dilemmas when taking care of racist patients since health care staff are bound by a duty of equal care for all patients. Strategies described by staff include working harder to prove their competence and faking, blocking or hiding their emotional responses to their experiences of racism. The emotional labor implied by these strategies could be intense and have negative effects on health. It is therefore paramount to create spaces where racism can be safely discussed to develop a safe healthcare environment for the benefit of staff and patients.